ISAR-SAFE: A randomized, double-blind, placebo-controlled trial of 6 vs. 12 months of clopidogrel therapy after drug-eluting stenting - Schulz-Schuepke, Stefanie; Byrne, Robert A.; Ten Berg, Jurrien M.; Neumann, Franz-Josef; Han, Yaling; Adriaenssens, Tom; Toelg, Ralph; Seyfarth, Melchior; Maeng, Michael; Zrenner, Bernhard; Jacobshagen, Claudius; Mudra, Harald; et al. (European Heart Journal, 2015)
Background In patients receiving aspirin, the optimal duration of clopidogrel therapy after drug-eluting stent (DES) implantation remains unclear. Methods This multicentre, randomized, double-blind, placebo-controlled trial tested the hypothesis that in patients undergoing DES implantation, 6 months of clopidogrel is non-inferior to 12 months in terms of clinical outcomes. At 6 months after DES implantation, patients on clopidogrel were randomly assigned to either a 6-month period of placebo or an additional 6-month period of clopidogrel. The primary endpoint was the composite of death, myocardial infarction, stent thrombosis, stroke, and thrombolysis in myocardial infarction major bleeding at 9 months after randomization. Results Owing to slow recruitment and low event rates, the trial was stopped prematurely after enrolment of 4005 of 6000 planned patients. Of 4000 patients included in the final analysis, 1997 received 6 months of clopidogrel and 2003 received 12 months. The primary endpoint occurred in 29 patients (1.5%) assigned to 6 months of clopidogrel and 32 patients (1.6%) assigned to 12 months, observed difference â '0.1%, upper limit of one-sided 95% confidence interval (CI) 0.5%, limit of non-inferiority 2%, P for noninferiority <0.001. Stent thrombosis was observed in five patients (0.3%) assigned to 6 months of clopidogrel and three patients (0.2%) assigned to 12 months; hazard ratio (HR) 1.66, 95% CI: 0.40-6.96, P = 0.49. Thrombolysis in myocardial infarction major bleeding was observed in 4 patients (0.2%) assigned to 6 months clopidogrel and 5 patients (0.3%) assigned to 12 months; HR 0.80, 95% CI: 0.21-2.98, P = 0.74. Conclusions In the present trial, characterized by low event rates, we did not observe a significant difference in net clinical outcome between 6 and 12 months of clopidogrel therapy after DES implantation. However, the results of the trial must be considered in view of its premature termination and lower than expected event rates. The trial is registered with ClinicalTrials.gov, Identifier: NCT00661206.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Clopidogrel; Double-blind; Drug-eluting stent; Dual antiplatelet therapy; Randomized trial; Stent thrombosis